1906 Ga. Laws 600-01, § 27 - (:unkn) unknown (General Publisher, 1906)
Granted the mayor and aldermen the power and authority to regulate and prevent the storage of gunpowder, tar, pitch . . . Or other combustible or explosive substances within city limits. Also granted the authority to reguate lights in stables, shops, or other places. Also granted the authority to regulate bonfires, fireworks, firecrackers, torpedoes, skyrockets, roman candles, firing of guns, pistols, anvils, and every kind of gaming or hunting within city limits.
--
Keywords: GUN POWDER STORAGE